Determinants of Carbon Tax Implementation - Whedy Prasetyo (Jurnal Reviu Akuntansi dan Keuangan, 2022)
Empirically this study examines the relationship between carbon tax implementation with several variables, namely voluntary awareness, behavior change, business performance, business size and business growth. The multiple regression model analysis is based on 52 respondents of companies in East Java that run forestry, energy and transportation businesses in Malang Raya (Malang Regency, Malang City, Batu City), Pasuruan Regency and Blitar Regency. The results showed that the implementation of the carbon tax was significantly and positively associated with voluntary awareness and business size, and significantly and negatively associated with business performance. The results of the study did not succeed in supporting the hypothesis of a relationship between the implementation of carbon taxes with behavioral changes and business growth. These results indicate that the carbon tax implementation a based on the polluters-pay principle takes place. A philosophy that reflects of carbon tax function as a sustainable activity towards being more efficient, low-carbon and environmentally friendly. Internal awareness of Taxpayer regarding carbon emission rates application or carbon pricing in the business activities carried out. The economic value of carbon that influences the realization Sustainability Report implementation.